MANAJEMEN PEMBELAJARAN AGAMA MELALUI PEMBIASAAN SHALAT DHUHA DI SEKOLAH DASAR NEGERI MEGA ELTRA - Imroatul Fatihah (IAIN Syekh Nurjati Cirebon, 2019)
Abstract Islamic religious learning should not be merely delivering material, but also instilling values and implementing it. In fact, so far the learning of Islam in schools is more limited to knowledge, because it is not managed properly, so it does not change behavior. However, something different happened in State Elementary School Mega Eltra, learning of Islamic religion through the habituation of the dhuha prayer could already be carried out in good learning management, even in conditions of limited religious facilities. For this reason, this research was intended to reveal more about religious learning through the habituation of the dhuha prayer in the Mega Eltra State Elementary School. This research was descriptive qualitative. The instruments were in-depth observation, in-depth interviews, and documentation. Data analysis was carried out through data collection, data reduction, data display, and data conclusions. The findings showed that principals and religious teachers plan religious learning through curriculum development and meetings. Religious learning through habituation of dhuha prayer in state elementary school Mega Eltra was carried out in good management. It was indicated by students’ enthusiasm taking ablution and performing dhuha prayer. Dhuha prayer was held in Islamic Education subjects. Dhuha prayer was carried out by students of grades 2 to 6. However, the place of worship was inadequate. Regularly, evaluations were carried out at teacher meetings. Keywords: practice, value, example